The application of the Suffolk Reading Scale (2) on South African learners. - Ramaahlo, Maria (My University, 2011)
The field of psychometrics in South Africa faces many challenges. Among these are, that practitioners in the field of psychology do not always have access to standardised assessments for the South African context. Imported assessments pose various biases to South Africa’s multilingual and multicultural situations, hence the need for test adaptation. The Suffolk Reading Scale (2) (SRS2) is an English proficiency assessment that measures reading comprehension. English, being the language of learning and teaching in most South African schools, makes the SRS2 a significant gain to practitioners and the field of psychometrics. Consequently, this research aimed to narrow the gaps in this area of knowledge and contribute to it by evaluating the applicability of the SRS2 as a measure of reading comprehension for South African learners. Primary school learners in Kwa-Zulu Natal were administered the SRS2. The purpose of the study was to ascertain the degree of reliability of the SRS2. Of the 338 participants, 51.9 percent (n=140) of the sample were female, and 48.1 percent (n=130) were male. Sixty-six percent (n=164) of the participants spoke English as an Additional Language (EAL), while thirty-four percent (n=83) spoke English as a first language (EFL). Results indicated a significant difference in performance between EFL and EAL learners, whereby EAL learners performed lower than EFL learners. However there was no difference in performance between female learners and their male counterparts on individual items of the SRS2. The SRS2 proved to have a suitable internal consistency; however questions of bias do arise.
Keywords: Psychometrics; Reliability; Standardized Assessments; Reading comprehension